2017
DOI: 10.3390/en10040440
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of an Organic Rankine Cycle with Adjustable Working Fluid Composition, a Volumetric Expander and a Recuperator

Abstract: Conventional Organic Rankine Cycles (ORCs) using ambient air as their coolant cannot fully utilize the greater temperature differential available to them during the colder months. However, changing the working fluid composition so its boiling temperature matches the ambient temperature as it changes has been shown to have potential to increase year-round electricity generation. Previous research has assumed that the cycle pressure ratio is able to vary without a major loss in the isentropic efficiency of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Figure 2 shows the T-s diagram of the highest efficiency case with the regenerative portion of the cycle highlighted in green. Figure 3 shows a comparison between the highest efficiency experimental case (i.e., a regenerative cycle arrangement) and the theoretical cycle predicted by the thermodynamic model [32]. Several things can be observed from this figure.…”
Section: The Test Case With Highest Thermal Efficiencymentioning
confidence: 97%
See 1 more Smart Citation
“…Figure 2 shows the T-s diagram of the highest efficiency case with the regenerative portion of the cycle highlighted in green. Figure 3 shows a comparison between the highest efficiency experimental case (i.e., a regenerative cycle arrangement) and the theoretical cycle predicted by the thermodynamic model [32]. Several things can be observed from this figure.…”
Section: The Test Case With Highest Thermal Efficiencymentioning
confidence: 97%
“…The case with the highest thermal efficiency was achieved using a regenerative cycle with a heat source temperature of 90 • C. The results of the case with the maximum efficiency are given in Table 3, and also as a T-s diagram, as shown in Figure 2. Then, they are compared with the theoretical performance of a cycle calculated using the authors' thermodynamic model [32] as shown in Figure 3. As shown in Table 3, the heat source and heat sink temperatures, the key control parameters, are respectively set as 90 • C and 7 • C in both experiments and simulations.…”
Section: The Test Case With Highest Thermal Efficiencymentioning
confidence: 99%
“…Therefore, the working fluid phase entering the turbine is conditioned at a fraction of 100% with a maximum temperature limit below of geothermal temperature (100 o C). Besides that, the critical temperature also has a significant effect on the pressure [22]. By using the calculations in the REFTROP, the range of allowable TIP values for each working fluid can be seen in FIGURE 4.…”
Section: Analysis Of Working Fluid Conditions Entering Turbinementioning
confidence: 99%
“…Similar findings were reported in the previous studies. [38][39][40] Thus, constant isentropic efficiency is not a good assumption for heat recovery application from a dynamic operating machine such as ICEs, having varying heat availability depending upon the size, speed and load.…”
Section: Selection Of Operating State Point For the Expander Inletmentioning
confidence: 99%